Famous and Forgotten: Soviet Sociology and the Nature of Intellectual Achievement under Totalitarianism - Sokolov, Mikhail (Serendipities. Journal for the Sociology and History of the Social Sciences, 2020)
For decades Soviet and later post-Soviet sociology was dominated by a cohort of scholars born between 1927–1930 (Grushin, Kon, Levada, Ossipov, Yadov, Zaslavskaya). The origins of their prominence and the character of their recognition offers a puzzle as it seemingly defies conventional ideas about where academic renown comes from. Academic prominence is usually associated with either intellectual leadership or skillful manipulation of the academic power structures. Neither of these stories describes the peculiar pattern of recognition of the giants of Soviet sociology whose fame persisted after they retired from administrative responsibilities and in spite of their ideas from the Soviet era being almost forgotten. The hypothesis developed in this paper holds that this peculiar form of fame emerges from the unique position sociology held in Soviet society. The paper introduces a distinction between natural and intentional secrecy and argues that while most of Western sociology specialized in natural secrecy, Soviet sociology had to deal with intentional secrecy resulting from conscious attempts to conceal the dismal realities of state socialism. The pervasiveness of secrecy during the Soviet era resulted from the central legitimizing myth of Soviet society describing it as built following a scientifically devised plan. This legitimation allowed Soviet sociology to emerge and develop with an unparalleled speed, but, at the same time, it explains why sociology was seen as having considerable subversive potential and faced periodic repressions. This political environment accounts for Soviet sociology’s unique intellectual style as well as for the fact that its central figures remained in the disciplinary memory as heroic role models, rather than as authors of exemplary texts.